Методы синтеза с использованием литийорганических соединений - Уэйкфилд Б. Дж. (Мир, 1991)
Экземпляры: КХ (20110930) / Инвентарный номер: 996071 / Цена: 5.12 / Сис.шифр: 24.2 / Авт.знак: У 97 / ГРНТИ: 31 / ББК: 24.23